Screening for head and neck tumors in patients with esophageal squamous cell carcinoma and vice versa: a nationwide survey among medical specialists - van Tilburg, Laurelle; van den Ban, Sophie A.; van de Ven, Steffi E.M.; Sewnaik, Aniel; Bruno, Marco J.; Spaander, Manon C.W.; Baatenburg de Jong, Robert J.; Koch, Arjun D. (Endoscopy International Open, 2022)
Background and study aims Retrospectively, minimally 5% of patients with esophageal squamous cell carcinoma (ESCC) and 11 % with head and neck squamous cell carcinoma (HNSCC) in Western countries developed a second primary tumor (SPT). SPT screening in ESCC and HNSCC patients is not implemented routinely in daily practice in many Western countries. This study aimed to assess medical specialist knowledge and opinions regarding screening for head and neck SPTs (HNSPTs) in ESCC patients and vice versa in the Netherlands.Methods A nationwide survey among gastroenterologists and head and neck (HN) surgeons was conducted between December 2020 and March 2021. The survey consisted of 27 questions and focused on knowledge of medical specialists of the prevalence and opinions toward implementing screening for HNSPTs in ESCC patients and vice versa. Results One hundred twenty-eight gastroenterologists (20.5 %) and 31 HN surgeons (50.0 %) completed the survey. The expected median prevalence of HNSPTs in ESCC was 7.0 % (interquartile range [IQR]: 5.0–15.0) among gastroenterologists and 5.0 % (IQR:3.0–8.0) among HN surgeons. For ESPTs in HNSCC, the expected median prevalence was 9.5 % (IQR: 5.0–12.0) among gastroenterologists and 4.0 % (IQR: 2.0–5.0) among HN surgeons. Screening for HNSPTs and ESPTs was considered promising by 35.2 % and 39.6 %, respectively, which increased to 54.7 % of the specialists after providing incidence data on SPTs. Of the HN surgeons, 41.3 % felt they were as capable as gastroenterologists of performing esophageal screening.Conclusions This Dutch nationwide survey revealed a lack of knowledge and different perspectives among specialists about screening to detect SPTs in ESCC and HNSCC patients. Adequate education seems essential to increase awareness among specialists and improve SPT detection, independent of the need for implementation of screening for SPTs in ESCC and HNSCC patients.